A Novel Approach for Rehabilitation of a Subtotal Maxillectomy Patient with Immediately Loaded Basal Implant-Supported Prosthesis: 4 Years Follow-Up - Motaz Osman; Abdelnasir G. Ahmad; Fadia Awadalkreem (Case Reports in Dentistry)
The prosthetic rehabilitation of maxillary defect can be achieved successfully by using an implant-supported prosthesis. The use of remote bony areas such as the zygomatic bone in cases of large defects provides an innovative substitute for free vascularized osteocutaneous flaps and the solution to flap failures. This report describes the rehabilitation of a 22-year-old female with a subtotal maxillectomy using an immediately loaded basal implant-supported prosthesis. Four basal cortical screw implants (BCS®) are inserted; 1 on the contralateral nasal floor, 2 implants in the pterygoid plates, and the last in the zygomatic bone using cone beam computed tomography scans. The prosthesis was constructed and cemented in 3 days. The surgical and prosthetic procedures were performed without any obstacles. After 4 years in function, the patient was highly satisfied with the treatment as it improved her mastication, speech, aesthetic and returned her self-esteem. To our knowledge, this is the first clinical report detailing the use of basal implant-retained obturator in a subtotal maxillectomy patient.